THE EFFECT OF PARTIAL REPLACING COW DUNG WITH WASTE CORN ON VARIOUS DOSAGES OF LIQUID ORGANIC FERTILIZER ON GROWTH AND YIELD OF Asystasia gangetica (L.) subsp. Micrantha - R. A., Bernardi; Duarsa, M. A. P.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika, 2024)
This research is aimed to know the effecet of partial replacing cow dung with waste corn on various dosages on growing and yield of Asystasia gangetica (L.) subsp. Micrantha. The research was held on a greenhouse, Research Station, on Jalan Raya Sading, Kecamatan Mengwi, Kabupaten Badung, Bali for three months. It was started from thei preparation until data retrieval using a completely randomized design with a split plot pattern two factors and four replication. It was given the combination of types and dosages of fermented cow dung liquid organic fertilizer. The main factor (main plot) was cow dung which is cow dung + water (KS1), cow dung + EM4 (KS2), and cow dung + EM4 + waste of corn (KS3) and the sublot factor was the dosage of fertilizer, which is no fertilizer (D0), 10.000 l ha-1 (D1), 20.000 l ha-1 (D2) and 30.000 l ha-1 (D3). The variables oberserved were growt variable, yield, and characteristic of growing of Asystasia gangetica (L.) subsp. Micrantha. The research showed that partial replacing cow dung with waste corn on various dosages did not interct on growth and yield Asystasia gangetica (L.) subsp. Micrantha. Partial replacement of cow dung with corn waste can be used for making liquid organic fertilizer. The fertilizer dose 20.000 (D2) l ha-1 tend to give the best growth and yield of Asystasia gangetica (L.) subsp. Micrantha compare to other doses. From this research it can be concluded that partial replacement cow dung with waste corn can be used to make liquid organic fertilizer and fertilizer dose 20.000 l ha-1 give the best growth and yield for Asystasia gangetica (L.) subsp. Micrantha.